No Evidence of Cancer or Cancer Markers 3 Years After Receiving a Non-Reportable Cell-Free DNA Sequence Analysis During Pregnancy - Check, Jerome H. (Archives of Clinical and Medical Case Reports, 2025)
The blood test performed in pregnant women who are at least 10 weeks from conception that measures cell free DNA from the placenta that can detect fetal aneuploidy that could lead to live deliveries (especially for aneuploidies e.g., trisomy 13,18, and 21) is known as non-invasive prenatal testing (NIPT). When this test is not able to be interpreted, if there are no fetal anomalies present or benign tumors e.g., fibroids, researchers have found a high percentage of various cancers in these women. Even in the low percentage of women found who do not have obvious cancer at the present time, or a known non-malignant etiology for the uninterpretable NIPT, thereafter is the possibility that an occult cancer is present and will manifest shortly. Presented is a case where there is still no evidence of cancer 2 years post-partum despite an unreportable NIPT (x2).